2012
DOI: 10.1104/pp.112.199307
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Distribution and Speciation in the Hyperaccumulator Astragalus bisulcatus and Associated Ecological Partners    

Abstract: The goal of this study was to investigate how plant selenium (Se) hyperaccumulation may affect ecological interactions and whether associated partners may affect Se hyperaccumulation. The Se hyperaccumulator Astragalus bisulcatus was collected in its natural seleniferous habitat, and x-ray fluorescence mapping and x-ray absorption near-edge structure spectroscopy were used to characterize Se distribution and speciation in all organs as well as in encountered microbial symbionts and herbivores. Se was present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 53 publications
5
55
0
Order By: Relevance
“…Previous studies have demonstrated that hyperaccumulators were characterized by a high leaf Se concentration, and a higher shoot:root Se concentration ratio [28,29]. Valdez et al [30] reported that as a Se hyperaccumulator, the pattern of total Se concentration in Astragalus bisulcatus follows the order root < leaf < stem. Under 24 mg kg −1 Se, the Se concentration in the roots (31.36 mg kg −1 ) was 3.17 and 7.57 times higher than those in leaves and stems, respectively (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hyperaccumulators were characterized by a high leaf Se concentration, and a higher shoot:root Se concentration ratio [28,29]. Valdez et al [30] reported that as a Se hyperaccumulator, the pattern of total Se concentration in Astragalus bisulcatus follows the order root < leaf < stem. Under 24 mg kg −1 Se, the Se concentration in the roots (31.36 mg kg −1 ) was 3.17 and 7.57 times higher than those in leaves and stems, respectively (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…It is feasible that the Se hyperaccumulators, given enough time, can influence Se speciation in surrounding soil in a radius of 10 m or more. Microbes may additionally affect soil Se speciation by converting inorganic soil Se to organic forms, and by converting organic Se deposited by hyperaccumulators into inorganic forms (Lindblom et al 2012). It has been reported for Symphyotrichum eatonii growing in Se-containing reclaimed mine soil, that rhizosphere soil and plant roots contained relatively more selenate (+6), while bulk soil contained more reduced Se (-2, 0) (Oram et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The canopy of individual hyperaccumulators at Pine Ridge Natural Area reaches up to 0.8 m in diameter, and the plants often occur in clusters. Their litter may be spread by wind, and Se ingested from hyperaccumulators (live or litter) may be spread by various detrivores and herbivores Freeman et al 2006a;Valdez Barillas et al 2012). The soil sample collected next to non-hyperaccumulators was on average 10 m away from Se hyperaccumulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in leaves of Stanleya pinnata , Se was present almost exclusively as MeSeCys (Freeman et al, 2006a). In the hyperaccumulator Astragalus bisulcatus , Se was present mainly as organic (C‐Se‐C) compounds in roots, stems, and leaves (Valdez Barillas et al, 2012). An important difference in Se speciation between hyperaccumulators and non‐accumulators is potentially the form of organoselenium present (e.g., LeDuc et al, 2004), although XAS techniques often lack the sensitivity to differentiate between such forms.…”
Section: Determining the Distribution And Speciation Of Trace Metal(lmentioning
confidence: 99%